A pena de galés na capital paulista (1830-1850): livres e escravizados condenados a uma pena de trabalho forçado na cidade de São Paulo - Santos, Alex de Jesus dos (2021)
This research focuses on the penalty of galleys in the city of São Paulo, in the period from 1830 to 1850. By galleys, it is understood a penalty inserted in the Brazilian Criminal Code of 1830, which the condemned should be reclused in a prison and leave it daily to provide forced public services, chained by the feet, together or separately, under the supervision of a guard. We aim to analyze the galleys penalty found in the Brazilian Criminal Code of 1830, as well as to understand its practical application in the city of São Paulo, from the prisoners sentenced to that penalty inmates in the Capital Public Jail and the use of the sentence by the Town Hall. In this context, we try to answer some questions: i-According to the potitical, legal and historicalsocial point of view what factores explain the presence of galleys penaulty in the Criminal Code of 1830? ii- What were the condemned profile and them utilization imprisioned on the Public City Jail?; iii- what are the implications of the galleys penalty for the city of São Paulo ?; ivthe use of convicts sentenced to galleys in the city of São Paulo implies that it has become, in the first 20 years of the Code, a punitive city ?. Therefore, we used, as a documentary source, the Criminal Code of 1830, the Criminal Procedure Code of 1832, the Proceedings of the Annals of the General Assembly from 1826 to 1830, the Book of Entry and Exit of Prisoners of the Capital of São Paulo; the Minutes of the Municipality of São Paulo and the General Records of the São Paulo Town Hall, both from the period corresponding to this research. We adopt the theoretical assumption that understands the penalty, punishment, as a form of coercion and social order, which aims at the control and surveillance of society, but, understanding that at the same time that there is surveillance, control and coercion, there is also from the individuals part the creative attitude, the resistances that are forged in the daily experiences of the day to day social or even in the punitive day of the sentence